Politics of Difference: Ethnicity and Social Class Within The Indonesian Middle Class in Digital Era - Thung Ju Lan (Antropologi Indonesia, 2020)
Today the issue of ethnicity is considered ‘weaker’ compared to religious issues, particularly after the 2017 Jakarta Governor Election which was followed by the emergence of the so-called 212 Movement. Nevertheless, the fact shows that it’s as strong as ever. The issue of socio-economic gap between ethnic groups is complicated by digital divide between those with access to social media and those without. Information and opinion are mostly constructed by surveys conducted among those with access to internet or social media. As such, group differences are not marked by poverty per se like the previous era. Politics of difference has been dictated by new type of ethnicity, namely class-based ethnicity. In this article I would like to discuss this topic within the context of the changing Indonesian middle class and their approach to religiosity as a defining trait of their identity.